Rancang Bangun Software Universal Astrolabe Berbasis Javascript dan Uji Akurasinya dalam Hisab Arah Kiblat - Nahwandi, M. Syaoqi; Setyawan, Edy; Nadirin, Akhmad (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2024)
The astrolabe, as a classical astronomical instrument, holds significant historical and educational value, yet its use has become limited due to technological advancements. This study aims to develop a JavaScript-based Universal Astrolabe software to digitize the functions of a physical astrolabe, with a focus on testing the accuracy of Qibla direction calculations. The Research and Development (R&D) method was implemented through stages of needs analysis, design, implementation, and accuracy testing. Test results from three locations (Cirebon, Kuala Lumpur, Istanbul) showed minor discrepancies (0°1'56